Topical medium-length PDRN enhances dermal extracellular matrix repair in photodamaged skin via PI3K–Akt/TGF-β–regulated pathways - Rui Ye; Qianqian Wang; Le Du; Li Li; Fan Hu (PLoS ONE, 2026)
Chronic ultraviolet (UV) exposure disrupts dermal fibroblast function and extracellular matrix (ECM) homeostasis, driving the structural features of photoaged skin. Polydeoxyribonucleotide (PDRN) has shown regenerative effects in injectable applications, but the mechanism and delivery of topical PDRN remain insufficiently defined. This study investigated the mechanism, skin delivery, and efficacy of a medium-length PDRN preparation (PDRN-850K) in photodamaged skin. Pathway activation was examined in basal human dermal fibroblasts using western blotting, gene expression analysis, and pharmacological inhibition. Skin delivery was assessed by confocal Raman spectroscopy in a reconstructed epidermal model and by complementary ex vivo and in vivo penetration studies. Tissue-level effects were assessed in a UV-irradiated human ex vivo skin model. Clinical efficacy was evaluated in a randomized, double-blind, split-face study comparing 0.1% PDRN-850K eye cream with 0.1% retinol over 28 days. PDRN-850K activated PI3K–Akt, TGF-β/Smad, and autophagy-related signaling in basal fibroblasts, and inhibition of these pathways reduced ECM gene induction. Raman analysis demonstrated time-dependent distribution of PDRN-associated signal into viable epidermal regions, with additional support from FITC-labeled porcine skin and pilot in vivo human Raman studies. In UV-irradiated ex vivo skin, PDRN-850K increased viable epidermal thickness and upregulated multiple collagens, elastic fiber–associated proteins, and YAP. Clinically, PDRN-850K achieved approximately two-fold greater improvements in periocular wrinkles, dermal thickness, density, and eye bag parameters compared with retinol, with good tolerability. These findings support PDRN-850K as a topical pro-repair approach for photodamaged skin.